PENDAMPINGAN KAUM MUDA GEREJA DALAM PENCARIAN PASANGAN HIDUP - Mieke Yen Manu; Irene Elvira Daik; Anggreani N. Paat; Octovianus Liu (Jurnal PKM Setiadharma, 2022)
Finding a life partner is often considered a private matter that does not need to be discussed publicly. In contrast, the process of choosing a life partner is a crucial stage before arriving at marriage. Mistakes in choosing a life partner will be borne for life. The church needs to take preventive action by educating young congregations to understand the basic Christian principles in choosing a life partner. This Community Service activity aims to strengthen partners' understanding regarding choosing a life partner, especially among church youth. This activity was carried out in two forms: seminars on the basic principles of choosing a life partner in Christian theology and the psychological perspective, and group assistance to hear partners' problems regarding choosing a life partner. The results showed that the participants understood the seminar material well, while the results of group assistance revealed that the main obstacle for participants was the relationship between different religious statuses. According to God's word, the solution offered by the service team was that participants need to consider the various harmful effects that were more likely to arise from an unbalanced relationship.